The impact of user-generated content in the fashion industry: A case study of SHEIN and PrettyLittleThing - Chloe Carr (Connectist Istanbul University Journal of Communication Sciences)
The rise of online shopping has encouraged online retailers to discover new ways to ensure consumers have a positive experience when searching for information within the competitive landscape. User-generated content (UGC) can be conveyed in a variety of formats and contexts, such as reviews, photos, forum posts, testimonials, and much more (Fader & Winer, 2012). The purpose of this research is to investigate and compare SHEIN, which hosts the functionality to post UGC in the form of reviews with photos, and PrettyLittleThing, which does not allow the functionality for UGC in any form. Very limited literature explores UGC in the fashion clothing industry amongst the young, upcoming generations. To address this, a sample of 12 females aged 18 to 26-years-old participated in semi in-depth interviews to discover the impact of user-generated content on the information search stage of the consumer decision-making process. This research adds to the current UGC body of knowledge in the form of photos with reviews in the fashion industry via a case study context. The findings emphasize the positive influence UGC (in the form of reviews with photos) has on the information search stage of the consumer decision-making process.